Effects of reducing sedentary behaviour on back pain, paraspinal muscle insulin sensitivity and muscle fat fraction and their associations: a secondary analysis of a 6-month randomised controlled trial - Norha, Jooa; Sjöros; Tanja: Garthwaite; Taru; Laine, Saara; Verho, Tiina; Saunavaara, Virva; Laitinen, Kirsi; Houttu, Noora; Hirvonen, Jussi; Vähä-Ypyä, Henri; Sievänen, Harri; et al. (BMJ Publishing Group, 2025)
OBJECTIVES: Sedentary behaviour (SB) is a plausible intervention target for back pain mitigation. Therefore, this study aimed to investigate the effects of a 6-month SB reduction intervention on back pain and related disability outcomes, and paraspinal muscle (ie, erector spinae and transversospinales separately) insulin sensitivity (glucose uptake, GU) and muscle fat fraction (FF).
METHODS: Sixty-four adults with overweight or obesity and metabolic syndrome were randomised into intervention (n=33) and control (n=31) groups. The intervention group aimed to reduce SB by 1 hour/day (measured with accelerometers) and the control group continued as usual. Back pain intensity and pain-related disability were assessed using 10 cm Visual Analogue Scales and the Oswestry Disability Index (ODI) questionnaire. Paraspinal muscle GU was measured using 18-fluorodeoxyglucose positron emission tomography during hyperinsulinaemic-euglycaemic clamp. FF was measured using MRI.
RESULTS: Pain-related disability increased during the intervention in both groups. Back pain intensity increased significantly more in the control group than in the intervention group in which back pain intensity remained unchanged (group×time p=0.030). No statistically significant between-group changes in pain-related disability, ODI or paraspinal GU and FF were observed. In the whole study group, the change in daily steps was associated positively with the change in paraspinal muscle GU.
CONCLUSION: An intervention focusing on SB reduction may be feasible for preventing back pain worsening regardless of paraspinal muscle GU or FF.
TRIAL REGISTRATION NUMBER: NCT03101228.